Acupuncture combined with balloon dilation for post-stroke cricopharyngeal achalasia: A meta-analysis of randomized controlled trials - Luo, Jing; Huang, Bingjing; Zheng, Huiyan; Yang, Zeyu; Xu, Mingzhu; Xu, Zhenhua; Ma, Wenjun; Lin, Run; Feng, Zitong; Wu, Meng; Cui, Shaoyang (Frontiers in Neuroscience, 2023)
Background The purpose of this study was to systematically evaluate the effectiveness of acupuncture combined with balloon dilatation in patients with post-stroke cricopharyngeal achalasia (CPA) according to the effective rate, videofluoroscopy swallowing study (VFSS) score and standardized swallowing function assessment scale (SSA) score through Meta-analysis. Methods English and Chinese language literature published before July 24,2022 were searched in ten electronic databases. The identified articles were screened, data were extracted, and the methodological quality of the included trials was assessed. Using RevMan 5.4.1 software to perform Meta-analysis. Results 10 studies with 517 patients with post-stroke CPA were included. Meta-analysis showed that the effective rate of the experience group was higher than that of the control group [OR = 0.62; 95% CI (2.32, 13.05); I2 = 0%; p = 0.0001]. Compared to the control group, the SSA score was lower in the experience group [MD = −4.22; 95% CI (−4.57, −3.87); I2 = 42%; p < 0.00001]. In terms of VFSS scores, the experience group showed greater efficacy differences than control group [MD = 1.53; 95% CI (1.32, 1.75); I2 = 0%; p < 0.00001]. The subgroup analysis of VFSS score based on the average course of disease (<1 month vs. ≥1 month) showed no significant difference. The subgroup analysis based on average age (>60 years vs. ≤60 years) showed the VFSS score of the experience group was significantly higher than that of the control group, and the effect may be better in the subgroup older than 60 years. The subgroup analysis based on the treatment course (>30 days vs. ≤30 days) showed the VFSS score of the experience group was significantly higher than that of the control group, and the effect may be better in the subgroup the treatment course>30 days. Conclusion Acupuncture combined with balloon dilatation may be an effective method for treating post-stroke CPA. Compared with balloon dilatation, acupuncture combined with balloon can significantly improve the swallowing function of patients, and it is also effective for patients of different courses, ages, and treatment course, while patients over 60 years old and the treatment course over 30 days may have better clinical outcomes.